Generation and characteristics of internal fire whirl in a shaft model with two corner slits under microgravity conditions. Issue 12 (15th June 2017) - Huo, Y.; Chow, W.K.; Chow, C.L.
Abstract: Generation and characteristics of internal fire whirl (IFW) in a shaft model under microgravity are studied using Computational Fluid Dynamics (CFD). The shaft model has two diagonally opposite corner slits with an open roof and a 10-cm diameter heptane pool fire inside. Acceleration due to gravity is varied from normal value of g to 0.0125 g . Numerical simulation indicates that even under low gravity of 0.0125 g, circular air motion would still bring fuel to a high level to give a larger flame height in the shaft model, compared with that in free space under the same gravity environment, the ratio in flame height being about 1.5 except at very low gravity value. For IFW generated in the shaft model, the heat release rate, the maximum tangential velocity and the maximum axial velocity decrease slowly as gravity decreases when gravity is above 0.1 g . Below 0.1 g, these quantities decrease rapidly as gravity decreases. Reduction in gravity also changes the flame shape of IFW.